ANTHROPOMETRIC PROFILE OF ELITE U16 BASKETBALL PLAYERS - Ilias Blantas; Panagiotis Androutsopoulos; Konstantinos Papadopoulos; Konstantinos Lapsanis; Giannis Eleftheriadis; Panagiotis Alexopoulos (International Journal of Basketball Studies, 2022)
The purpose of the study was to examine and record the anthropometric profile of U16 elite male basketball players of national teams per competitive position as well as to compare the differences of anthropometric profiles between the playing positions. The study involved 17 young male basketball players (average weight 84 kg, average height 1.97 cm, average age 15.9 years). Players were classified according to their position in Guards (G: n = 7), Forwards (F: n = 6), and Centers (C: n = 4). The players participated in the Development Program of the Hellenic Basketball Federation in the year 2021 and were preparing for their possible selection and participation in the Greek National Team, which would participate in the U16 European Basketball Championship of the same summer. In order to determine the anthropometric profile of the elite players of the study, the following anthropometric characteristics were measured in each position: height, weight, wingspan, standing reach, body fat percentage and body mass index (BMI). The sample was analyzed separately for three different positions of the players, the Guards, the Forwards and the Centers. In the inductive analysis, the possible differences between the different positions of the players were examined. One-way analysis of variance (one-way ANOVA) was used to look for differences between the mean values ​​of the variables measured in relation to the athlete's position on the court. The main findings suggest that the anthropometric profile of the U16 male players of the Greek National Basketball Team is at a high level. Specifically, Guards recorded an average height of 190.29 ± 4.64 cm, weight 77.26 ± 5.91 kg and body fat percentage 10.33 ± 1.11 (%).Accordingly, Forwards recorded height of 197.5 ± 4.89 cm, weight 84.06 ± 10.62 kg,body fat percentage 9.85 ± 2.39 (%) and the Centers recorded height of 205.5 ± 3.11 cm, weight 94.99 ± 4.5 kg and body fat percentage 11.78 ± 1.95 (%).Furthermore, the findings showed that the players of the Center position were significantly superior in almost all anthropometric measurements compared to the other two positions. In particular, the Centers had the highest height, weight, body fat percentage and standing reach compared to the Guards and Forwards although they were younger. No differences were found in the other measurements.